(untitled) (The Eurasia Proceedings of Educational and Social Sciences, 2018)
In this study, the effect of SMART Board usage in the 7th grade Human and Environmental unit was investigated on students’ attitudes toward the environment. For research; two middle schools were used in Konya Province Hadim District. One of the schools was chosen as the control group and the other was chosen as the experimental group. The Environmental Attitude Scale was used as data collection tools. For 4 weeks, the students in the control group processed the Human and Environmental unit according to the traditional methods while the students in the experimental group were processed using the same unit smart board activities. The Environmental Attitude Scale was applied as a pre-test to determine the students’ attitudes toward the environment before the application started. After the application was completed, the same test was applied as a post-test to determine the students’ attitudes towards the environment. The obtained data were analyzed with SPSS 22 statistical package program and t-test was used in the evaluation of the obtained data. As a result of the analysis of the post-test data of the Environmental Attitude Scale, although the score of the experimental group was higher than that of the control group, there was no statistically significant difference between the experimental group and the control group. Therefore, it has been found that the use of SMART Board has not been effective in improving students’ attitudes towards the environment.